TRANSFER DEVICE FOR MAKING UP KERATIN MATERIALS (2014)
The present invention relates to a process for making up an area of human keratin materials using a makeup device comprising a deformable substrate bearing a transfer surface intended to come into contact with the keratin materials and configured to receive a coat of cosmetic ink. The process includes the following steps: a. depositing at least one cosmetic ink onto the transfer surface by means of at least one digital printer, b. placing the transfer surface in contact with the area to be made up by mechanical action, especially by exerting a pressure on a surface opposite the transfer surface, and c. moving the transfer surface away from the area of the human keratin materials after the ink has been transferred.